Emergence of an XDR Klebsiella pneumoniae ST5491 strain co-harboring NDM-5, MCR-1.1, tmexCD1-toprJ1, and a novel plasmid carrying CTX-M-15 - Fang, Yinfei; Li, Xiangchen; Wu, Zhaoxia; Fang, Yongjin; Wang, Yeping; Li, Xiaobing; Bu, Lihong; Chen, Keqiang; Shen, Kai; Ma, Yongjun; Wu, Mingjuan (Frontiers in Microbiology, 2025)
ObjectiveThe rapid emergence of antimicrobial resistance (AMR) in Klebsiella pneumoniae poses a significant global health threat. The study aimed to analyze and describe the genomic architecture and resistance mechanisms of an extensively drug-resistant (XDR) K. pneumoniae isolate, KP09, by focusing on plasmids that harbor multiple resistance genes, including tmexCD1-toprJ1, blaCTX-M-15, blaNDM-5, and mcr-1.1.MethodsThe KP09 strain, isolated from a clinical sample, was subjected to antimicrobial susceptibility testing and conjugation experiments. Whole-genome sequencing with both long- and short-read methods facilitated hybrid assembly for complete genome reconstruction. Bioinformatics analyses identified resistance genes, plasmid structures, and sequence types (STs), whereas comparative genomic analysis elucidated the context and dissemination mechanisms of resistance determinants.ResultsKP09 exhibited broad-spectrum resistance to carbapenems, colistin, eravacycline, and tigecycline, and only remained susceptible to cefiderocol. The conjugation experiments successfully produced four transconjugants, each carrying specific plasmids: JKP09-1 harbored the tmexCD1-toprJ1 gene, JKP09-2 harbored tmexCD1-toprJ1 and mcr-1.1 genes, JKP09-3 harbored the mcr-1.1 gene, and JKP09-4 harbored blaNDM-5 and mcr-1.1 genes. Genomic analysis revealed a novel IncFIA/IncFII/IncQ1 hybrid plasmid carrying blaCTX-M-15, along with a large conjugative plasmid encoding the tmexCD1-toprJ1 efflux pump. The blaNDM-5 and mcr-1.1 genes were located in separate IncX-type plasmids, suggesting independent dissemination pathways. Furthermore, KP09 was identified as a new sequence type, ST5491, closely related to the endemic ST15 clone. The comparative analysis highlighted the role of mobile genetic elements, such as IS26 and ISEcp1, in facilitating the spread of resistance genes.ConclusionThis study provides critical information on the genetic mechanisms that drive AMR in K. pneumoniae, including the identification of a novel blaCTX-M-15 encoding IncFIA/IncFII/IncQ1 hybrid plasmid and the emergence of the ST5491 strain. Understanding the genetic basis of resistance is essential to inform public health interventions and mitigate the impact of AMR.